ANALISIS IMPLEMENTASI KURIKULUM 2013 DI SMA NEGERI 3 REJANG LEBONG, BENGKULU - Gita Yolanda; Saidil Mustar; Deri Wanto (Paedagogia: Jurnal Pendidikan, 2020)
This study aimed at analyzing qualitatively the implementation of K13 curriculum which has long been applied in the state senior high school number 3 of Rejang Lebong. The data were garnered using observations and interviews for the sake of eliciting information to answer the proposed problem. The other technique considered important was documentation to see the curriculum-based depictions and loads in the existing documents. After the data were gathered, the selection of data was undertaken in order to be displayed in findings; the data were analyzed and discussed; and they were concluded as the ultimate answer to the formulated problem. The present study drew a conclusion that the implementation of k13 curriculum ran well although some obstacles were faced such as learning facilities. The entire school’s community seemed to be committed to carry out the mandate of this national educational system’s law such as training for teachers’ competence, doing the duties of making lesson plans in the form of RPP and syllabi, providing a monthly report concerning the implementation of learning by teachers, and carrying out evaluations alongside giving guidance for teachers’ performances.